2018
DOI: 10.1002/clc.22993
|View full text |Cite
|
Sign up to set email alerts
|

Advanced chronic kidney disease: Relationship to outcomes post‐TAVR, a meta‐analysis

Abstract: Chronic kidney disease (CKD) is associated with worse outcomes in high-surgical-risk patients undergoing transcatheter aortic valve replacement (TAVR). However, it is unclear whether this relationship is apparent in lower-surgical-risk patients. We sought to analyze existing literature to assess whether or not advanced CKD is associated with increased mortality or a greater incidence of adverse events (specifically major stroke, bleeding, and vascular complications). We searched PubMed and Embase (2008-2017) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…Based on the multivariable Cox analysis, we identified several baseline and procedurerelated factors as being independently associated with long-term mortality after TAVI (Table 4). Most of them are well known and have been previously described [16][17][18][19][20]. Interestingly, we found that balloon postdilatation was the independent predictor of long-term survival (HR 0.35; 95%CI: 0.16 -0.75; P = 0.008).…”
Section: Discussionsupporting
confidence: 53%
“…Based on the multivariable Cox analysis, we identified several baseline and procedurerelated factors as being independently associated with long-term mortality after TAVI (Table 4). Most of them are well known and have been previously described [16][17][18][19][20]. Interestingly, we found that balloon postdilatation was the independent predictor of long-term survival (HR 0.35; 95%CI: 0.16 -0.75; P = 0.008).…”
Section: Discussionsupporting
confidence: 53%
“…Several studies showed the association between severe or advanced CKD and increased mortality in patients undergoing TAVI. 5,7,[20][21][22] The role of AKI in predicting early and long-term outcomes among TAVI recipients has been also extensively reported. 10,17,18,23 Mortality rates at 30 days post-TAVI among patients experiencing AKI ranged from 10 to 30% compared with 2 to 15% for patients without AKI.…”
Section: Discussionmentioning
confidence: 99%
“…This raises a question about the real benefit from TAVR in this population. Intermediate-risk patients also benefit from TAVR in terms of lower AKI burden when compared to SAVR patients, but their advanced-stage CKD (>4) does not seem to be related to mortality 23…”
Section: Risk Factorsmentioning
confidence: 99%